Rancang Bangun Kerangka Tanaman Hidroponik Politeknik Negeri Batam - Pamungkas, Nurman; Widiastuti, Hanifah; Restu, Fedia; Leksonowati, Nur Fitria Pujo; Arifin, Nurul Laili; Muvariz, Mufti Fathonah; Ulfah, Nurul; Widodo, Widodo; Baharudin, Budi; Fajrin, Aulia; Fyona, Annisa; Kamsyah, Domi; Gemala, Mega; Rosbandrio, Wowo; Aryswan, Adhe; Siregar, James; Saputra, Hendra; Irawan, Benny Haddli; Saputra, Ihsan; Ariyanto, Nugroho Pratomo; Mutiarani, Mutiarani (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2023)
The hydroponic pilot project in the Batam State Polytechnic area was motivated by problems with economic conditions and declining health conditions during the Covid-19 pandemic. This project is expected to support the "growing your own food movement" in an effort to reduce unemployment, increase food security and a healthy lifestyle. The hydroponic method was chosen because it is very easy to do and does not require a large area of "‹"‹land. In this community service activity, a hydroponic plant building framework will be made as a prototype of an efficient and efficient hydroponic building so that it can be used by the wider community. This activity is also useful for applying design knowledge as one of the PbL activities carried out by CAD, CNC, CAM, and Fabrication Engineering courses in the Mechanical Engineering Department, so that it can become an arena for higher education participation to support people's lives. The method of implementing this community service activity is to make observations to find a suitable area to build a hydroponic plant house, then the results of the observations are poured in the form of a design by utilizing software so that the materials needed and the shape of the framework that is built can be known. The last activity is making a hydroponic plant place. This activity is planned to be carried out from April to November 2021. Based on the results of the evaluation of the service program questionnaire for product distribution, it is known that the majority of respondents are satisfied with the products produced.